ANALYSIS OF THE USE OF DIGITAL PAYMENT METHODS (QRIS) IN MIE SAMYU MSMES IN INCREASING CONSUMER SATISFACTION - Moh. Idil Ghufron; Hanin Fara Atiqoh; Dwi Nurul Hidayati (Nurul Jadid University, 2025)
Digital transformation in the financial sector has encouraged the presence of technology-based payment methods, one of which is the Quick Response Code Indonesian Standard (QRIS). This innovation is designed to simplify and accelerate the transaction process, as well as increase financial inclusion, especially for Micro, Small and Medium Enterprises (MSMEs). This study aims to analyze the extent to which the use of QRIS digital payment methods affects the level of consumer satisfaction in Mie Samyu MSMEs, a culinary business that has implemented QRIS in its operations. This research uses a qualitative paradigm with a case study approach. Data was collected through in-depth interviews, participatory observations, and documentation of Mie Samyu MSME owners, employees, and customers. The data analysis technique used is thematic analysis, which aims to identify patterns of consumer perception of the use of QRIS in their transaction experience. This research is expected to be able to fill the empirical gap regarding the impact of the use of QRIS on the MSME sector specifically and answer the research gap in the academic literature related to the relationship between digital payment methods and consumer satisfaction in the culinary sector. The results of this research are also expected to make a practical contribution in encouraging the digitalization of MSMEs in a sustainable manner and become a reference for public policies in optimizing the use of QRIS as a national digital economy instrument.